Nuclear magnetic resonance of biological macromolecules. - James, Thomas L. (Methods in enzymology, 2005)
The critically acclaimed laboratory standard, Methods in Enzymology, is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. The series contains much material still relevant today - truly an essential publication for researchers in all fields of life sciences. Nuclear Magnetic Resonance of Biological Macromolecules, Part C is written with a "hands-on" perspective. That is, practical applications with critical evaluations of methodologies and experimental considerations needed to design, execute, and interpret NMR experiments pertinent to biological molecules. * One of the most highly respected publications in the field of biochemistry since 1955 * Frequently consulted, and praised by researchers and reviewers alike * Truly an essential publication for anyone in any field of the life sciences.